Theoretical basis for the effective use of regional powers in sustainable economic development - Buriev Sardor Norovich (THE INNOVATION ECONOMY, 2026)
The article presents the scientific and theoretical definitions of the categories "economic growth" and "economic potential", their comparative analysis, as well as the importance of the economic potential of the region in ensuring sustainable development and economic growth, the main elements, the classification of economic potential and the directions of strategic management of the possibilities of its use.